Deceleration of the Competitiveness of Indonesian Youth in Facing Development Challenges Towards a Golden Indonesia 2045 - Meidianto, Rinaldy (Journal Research of Social Science, Economics, and Management, 2025)
Indonesia’s youth population, totaling approximately 64.22 million, represents a vital resource for achieving the national vision of Golden Indonesia 2045. However, youth competitiveness is declining due to persistent challenges such as high rates of NEET (Not in Education, Employment, or Training) at 23.78% and youth unemployment at 12.24%. These issues are compounded by limited access to quality education, vocational training, and digital skills, especially in rural and underserved regions. The study aims to analyze the factors contributing to this deceleration and propose evidence-based policy recommendations to improve youth empowerment through coordinated efforts between central and regional governments and collaboration with the private sector. Utilizing an Evidence-Based Policy approach, data were collected from primary interviews, national statistics, and secondary literature, and analyzed using the Urgency, Seriousness, and Growth (USG) framework and Cost-Benefit Analysis (CBA). The findings highlight the critical need for integrated policies that expand access to education and vocational training, enhance entrepreneurial opportunities, and strengthen institutional synergy across governance levels. Effective implementation of these policies is essential for sustainable youth development, equitable opportunity distribution, and maximizing Indonesia’s demographic dividend. This paper provides a strategic implementation framework for policymakers to accelerate youth competitiveness and foster active youth participation in national development.